2019
DOI: 10.1016/j.adro.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy Dose Escalation to Clinically Involved Pelvic Sidewall Lymph Nodes in Locally Advanced Rectal Cancer

Abstract: Purpose Lateral pelvic sidewall lymph nodes (PSW LN) may be involved in up to 24% of locoregionally advanced rectal cancers. PSW LN are not resected in total mesorectal excision (TME), and no standard of care regarding the management of PSW LN exists in the United States. We assessed our institutional experience of preoperative radiation therapy (RT) boost to clinically involved PSW LN that were not planned for resection. Methods and materials Data from all patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
(37 reference statements)
1
9
1
Order By: Relevance
“…Here, an attempt at an escalation radiation dose based on the regular dose of 56-58 Gy was prescribed to a subgroup of patients with baseline LLN SA ≥5 mm from 2015. In line with our study, a radiation dose boost for the clinical suspicious LLNs was reported in several studies (19,28,29). In gynecologic cancers, the radiation dose of LLN was boosted to 60 Gy and did not result in higher morbidity rates (28).…”
Section: A B D Csupporting
confidence: 89%
See 2 more Smart Citations
“…Here, an attempt at an escalation radiation dose based on the regular dose of 56-58 Gy was prescribed to a subgroup of patients with baseline LLN SA ≥5 mm from 2015. In line with our study, a radiation dose boost for the clinical suspicious LLNs was reported in several studies (19,28,29). In gynecologic cancers, the radiation dose of LLN was boosted to 60 Gy and did not result in higher morbidity rates (28).…”
Section: A B D Csupporting
confidence: 89%
“…To date, reports on LLN dose escalation in rectal cancer are limited. Only a small-scale study (involving 12 patients) with short-term LR was reported (19). In our study, for patients with LLN metastasis, the LR and LLR rates in the dose escalation subgroup were significantly lower, and size reduction was significantly better than in the nCT and nCRT subgroups.…”
Section: A B D Ccontrasting
confidence: 41%
See 1 more Smart Citation
“…Some Western clinicians believe that an irradiation boost may provide the extra enhancement required to treat LLNs without additional LLND surgery. 52 , 53 , 54 Just two studies have evaluated a boost in LLNs, with mixed results. Chen et al 53 studied 12 patients with suspicious LLNs, all of which had received a “boost” as treatment (3 × 5.4 Gy).…”
Section: Towards International Collaborationmentioning
confidence: 99%
“…The second study, also with only 12 patients, determined that a boost did not result in an increased risk of toxicity or perioperative complications. 54 However, more research is warranted before a boost should be considered part of a treatment schedule. Furthermore, with the potentiality that according to Ogura et al, 8 only 22% of internal iliac LLNs adequately respond to neoadjuvant treatment, the desired benefit of a boost may be limited.…”
Section: Towards International Collaborationmentioning
confidence: 99%